In Vivo Total Dose Analysis in Mice for BNCT Trial TRIGA Kartini Research Reactor Based Using PHITS - Ramadhan Valiant Gill S Balle (Fakultas Sains dan Matematika Universitas Kristen Satya Wacana, 2019)
Boron neutron capture therapy (BNCT) is an effective radiotherapy modality to kill cancer. BNCT can selectively kill cancer cells without damaging the healthy tissue around it by using alpha particle and lithium ion from the reaction of 10B(n,α)7Li. These particles have a track of more or less 5 to 9 μm which is the same as the cell diameter. In order to support the development of BNCT in Indonesia an in vivo simulation is performed in a simple mouse geometry containing a 4T1 breast cancer characteristic treated with BNCT using PHITS program. The Neutron source that was used in this simulation was based on TRIGA Kartini Research Reactor. The boron compound concentration in the tumor was varied from 20 ppm up to 90 ppm, and then the total dose was calculated in the mice. Total dose that the tumor received was 0.0161, 0.0168, 0.0175, 0.0182, 0.0185, 0.0188, 0.019, and 0.0191 Gy-Eq/s, respectively and the irradiation time to reach 50 Gy was 51, 50, 48, 46, 45, 45, 44, 44, 40 minutes respectively. This shows that the higher the concentration of boron compound in the tumor the higher the dose that mice received and irradiation time was decreased with the increase of the boron compound concentration.